THE INVESTIGATION OF REFUSAL STRATEGIES USED BY UNIVERSITY STUDENTS OF ENGLISH DEPARTMENT - Aulia Fitri; Asnawi Muslem; Saiful Marhaban (Universitas Syiah Kuala, 2020)
The aim of this research is to investigate the refusal strategy used by Acehnese EFL university students and how the interlocutor’s power status affects on it. The sample of this study were 25 students at fifth-semester of English language department of Syiah Kuala University. In collecting the data, this study used a discourse completion test consisting of 10 situations, and semantic formula were analyzed and categorized according to the Beebe, Takahashi and Uliss-Weltz (1990). The results show that the students used different manners in presenting the refusal strategies. In refusing the intelocutors, they tended to choose an indirect strategy by stating regret or saying 'sorry', and excuses or explanations, while the direct and adjunct strategies were the least to be used. Moreover, this study has also been shown that the interlocutor's status became a significant role in the number of strategies used for refusing. The higher the status of our interlocutor was, the more polite the use of refusal strategies the participants employed. Additional analysis revealed that the students’ culture greatly influences the presenting of their strategy in refusing. The study's results are expected to pave future research concerning English foreign language learners' refusal strategies.